Corporate Governance Practices and Disclosure of Risk Management Sharia Bank in Asean - Wiwik Utami; Lin Oktris; Rini Rini; Nur Wachidah Yulianti (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2021)
Abstract. The risks faced by Islamic banks are similar to conventional banks. Therefore, Sharia Banks must also carry out risk management disclosures. This study aims to examine the effect of governance, including the Sharia Supervisory Board, Independent Commissioner, Audit Committee, Risk Committee, the doubling of the Sharia Supervisory Board Position, and the frequency of meetings on the quality of risk management disclosures. The population is Sharia Banks in ASEAN; samples are selected purposively according to the data's completeness that can be accessed through the capital market website. Risk management disclosures are measured using the index of completeness of risk items revealed. Data analysis was performed using multiple regression analysis. The study found that the number of audit committees and meeting frequency had a significant and positive effect on the quality of risk management disclosures. The number of Sharia supervisory boards has a significant effect on the negative coefficient. Other governance variables do not affect risk management disclosures.Keywords: Sharia Bank, Corporate Governance, Risk Management, Disclosure.Abstrak. Risiko yang dihadapi bank syariah hampir sama dengan bank konvensional. Oleh karena itu, Bank Syariah juga wajib melakukan pengungkapan manajemen risiko. Penelitian ini bertujuan untuk menguji pengaruh tata kelola antara lain Dewan Pengawas Syariah, Komisaris Independen, Komite Audit, Komite Risiko, penggandaan Jabatan Dewan Pengawas Syariah, dan frekuensi rapat terhadap kualitas pengungkapan manajemen risiko. Populasinya adalah Bank Syariah di ASEAN. Sampel dipilih secara purposif sesuai dengan kelengkapan data yang dapat diakses melalui website pasar modal. Pengungkapan manajemen risiko diukur dengan menggunakan indeks kelengkapan item risiko yang diungkap. Analisis data dilakukan dengan menggunakan analisis regresi berganda. Hasil penelitian menyimpulkan bahwa jumlah komite audit dan frekuensi rapat berpengaruh signifikan dan positif terhadap kualitas pengungkapan manajemen risiko. Jumlah dewan pengawas syariah berpengaruh signifikan dengan koefisien negatif. Variabel tata kelola lainnya tidak mempengaruhi pengungkapan manajemen risiko.Kata Kunci: Bank Syariah, Tata Kelola Perusahaan, Manajemen Risiko, Pengungkapan.